THE DIFFERENCE OF SAMPLES OF ZІZYPHUS JUJUBA MILL., 1768 IN THE COLLECTION OF THE KHOROL BOTANICAL GARDEN - Кrasovsky, V. V.; Cherniak, Т. V.; Antonets, M. O.; Antonets, O. A. (Scientific Progress & Innovations, 2022)
Among the population of the forest-steppe zone of Ukraine, there is an increased interest in the growing of subtropical fruit plants, in particular, the Zizyphus jujuba Mill. For the gradual introduction of a new fruit plant into the culture, there is foremost a need to create a gene pool environment of the species involving methods of introduction and selection. A significant role in solving this problem is given to botanical gardens. They are the ones to introduce and select plants. One of the main directions of scientific research of the Khorol Botanical Garden is the introduction of subtropical fruit crops in the forest-steppe of Ukraine, where the collection of Z. jujuba plants was selected. It consists of 50 plants. They are 11 years old and have the life-form of a tree. Plants are planted in two rows, 4 meters apart, and with a 2 meters distance among plants on each row. The shape of the trees is improved by pruning and forming their trunks and crowns. Three-year hybrid seedlings of Z. jujuba were taken as planting material of the collection. The local middle-fruited specimen created as a result of several reproductive cycles was used as the source for winter hardiness. Hybrid seeds were harvested from it. Samples of large fruits were also used, but with defective seeds that definitely need protection from frost in the winter conditions of the forest-steppe of Ukraine. Valuable Z. jujuba genotypes such as Ta-Yang-Tsao and of the Vakhshsky varieties were used as hybrids as the source of large fruits. They were introduced by the transfer of vegetative material in the form of cuttings. The study on the difference of Z. jujuba samples was conducted after the morphological description of the collection during 2019–2021. The sample was considered excellent in the case of distinguishing it from others by the method of comparing the descriptions of the samples. The research revealed valuable genotypes, namely 11 samples different from those available in the collection. Among them, the most important elements of the novelty of the samples are namely short stature, small amount or absence of thorns, the size of the fruiting shoot, size of the leaf blade, size of the fruit, shape of the fruit, fruit weight, and the fruit’s juiciness. The Natural and climatic conditions of the forest-steppe of Ukraine contribute to the cultivation of selected samples. These samples are also characterized by high vegetation productivity and fruiting.